Strategies for Upgrading an Operator's Backbone Network Beyond the C-Band: Towards Multi-Band Optical Networks - Dimitris Uzunidis; Evangelos Kosmatos; Chris Matrakidis; Alexandros Stavdas; Andrew Lord (IEEE Photonics Journal, 2021)
Telecommunication networks are becoming the central linking institution of the Fourth Industrial Revolution. To cope with the associated capacity and connectivity challenges, transportation networks may explore the -neglected so far- remaining transmission bands in the second and third low attenuation windows of the optical fibre overcoming the C-band barrier. To assess the potential of optical multi-band transmission systems to upgrade a European Operator's network, we have developed a planning tool based on a routing engine that exploits a novel Physical Layer Aware, Routing, Modulation and Spectral Assignment algorithm. We considered unrepeatered transmission exploiting fibre amplifiers tailored to each transmission band. Taking into account the performance of close to commercialization fibre amplifier devices, we estimated the impact for the most detrimental effects in multi-band transmission like ASE accumulation, FWM and SRS. With the aid of this planning tool, we demonstrate the potential of multi-band systems to upgrade network capacity without compromising the connectivity between Core nodes, albeit new physical layer challenges. Nevertheless, it is shown that multi-band systems allow higher operational flexibility that may slow-down the need to deploy additional C-band fibres. Moreover, we have shown that the roll out of these multi-band systems could be planned in phases in order to limit first-day capital expenditure.